Re‐evaluation of target lipid model–derived HC5 predictions for hydrocarbons. (31st March 2018) - McGrath, Joy A.; Fanelli, Christopher J.; Di Toro, Dominic M.; Parkerton, Thomas F.; Redman, Aaron D.; Paumen, Miriam Leon; Comber, Mike; Eadsforth, Charles V.; den Haan, Klaas
Abstract: The target lipid model (TLM) has been previously applied to predict the aquatic toxicity of hydrocarbons and other nonionic organic chemicals and for deriving the concentrations above which 95% of species should be protected (HC5 values). Several concerns have been identified with the TLM‐derived HC5 when it is applied in a substance risk assessment context. These shortcomings were addressed by expanding the acute and chronic toxicity databases to include more diverse taxonomic groups and increase the number of species. The TLM was recalibrated with these expanded databases, resulting in critical target lipid body burdens and acute‐to‐chronic ratios that met the required guidelines for using species sensitivity distributions in substance risk assessment. The HC5 equation was further revised to consider covarying model parameters. The calculated HC5 values derived from the revised TLM framework were validated using an independent data set for hydrocarbons comprising 106 chronic values across plants, invertebrates, and fish. Assuming a sum binomial distribution, the 95% confidence limit for a 5% failure is between 0.8 and 9.2%. Eight chronic values fell below the HC5, corresponding to an excursion of 7.5%, which falls within the expected uncertainty bounds. Thus, calculated HC5s derived from the revised TLM framework were found to be consistent with the intended protection goals. Environ Toxicol Chem 2018;37:1579–1593. © 2018 SETAC